2020
DOI: 10.1111/pan.14044
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes from wake up safe, the pediatric anesthesia quality improvement initiative

Abstract: Background: Wake Up Safe, a Patient Safety Organization founded by the Society for Pediatric Anesthesia, collects data on serious adverse events along with demographic data from all pediatric patients receiving anesthesia care at participating institutions. This report reviews all events occurring between 2010 and 2015 and focuses on common adverse events that are anesthesia-related. Aims: Determine which adverse events were most common from 2010 to 2015 among participating Wake Up Safe institutions. Determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
0
19
1
1
Order By: Relevance
“…Perioperative pulmonary aspiration in children remains infrequent and is more likely in emergency situations than in elective surgeries. Its overall incidence in the pediatric population has been estimated to be 0.03%–0.1% 1‐3 . In order to decrease the risk of aspiration, healthy children undergoing elective surgery are traditionally kept fasting overnight to ensure that their stomach is empty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perioperative pulmonary aspiration in children remains infrequent and is more likely in emergency situations than in elective surgeries. Its overall incidence in the pediatric population has been estimated to be 0.03%–0.1% 1‐3 . In order to decrease the risk of aspiration, healthy children undergoing elective surgery are traditionally kept fasting overnight to ensure that their stomach is empty.…”
Section: Introductionmentioning
confidence: 99%
“…Its overall incidence in the pediatric population has been estimated to be 0.03%-0.1%. [1][2][3] In order to decrease the risk of aspiration, healthy children undergoing elective surgery are traditionally kept fasting overnight to ensure that their stomach is empty. Current guidelines recommend fasting of 6-h for solids, 4-h for breast milk, and 2-h for clear fluids prior to anesthesia.…”
mentioning
confidence: 99%
“…The US Society for Pediatric Anesthesia sponsors 'Wake Up Safe', a registry of defined serious adverse events occurring during the perioperative period [14]. Contributing institutions-currently 29 centers in Northern America-report data on patient demographics and adverse events, including a structured analysis of why these events occurred as well as their preventability [15]. The registry was established in order to identify areas in patient care in need of improvement [11].…”
Section: Quality Improvement In Pediatric Anesthesiamentioning
confidence: 99%
“…In addition, considering that the authors conducted a global review of perioperative cardiac arrests (Table 1), they did not include relevant and important articles found in the PubMed/Medline databases; examples include: Haché et al [ 21 ]; Jansen et al [ 22 ]; Kawashima et al [ 23 ]; Morita et al [ 24 ]; Strøm et al [ 25 ]; and Strøm et al [ 26 ].…”
mentioning
confidence: 99%
“…Again, the authors of the review did not include relevant articles found in the PubMed/Medline databases in the forest plot of the perioperative mortality rates (Figs. 2 and 3 are the same); examples include Boonmak et al [ 27 ], Habre et al [ 28 ], Haché et al [ 21 ], Jansen et al [ 22 ], Kawashima et al [ 23 ], Morita et al [ 24 ], Strøm al. [ 25 ], and Strøm et al [ 26 ].…”
mentioning
confidence: 99%